If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2(7r + -1r) = -116 Combine like terms: 7r + -1r = 6r 4 + 2(6r) = -116 Remove parenthesis around (6r) 4 + 2 * 6r = -116 Multiply 2 * 6 4 + 12r = -116 Solving 4 + 12r = -116 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 12r = -116 + -4 Combine like terms: 4 + -4 = 0 0 + 12r = -116 + -4 12r = -116 + -4 Combine like terms: -116 + -4 = -120 12r = -120 Divide each side by '12'. r = -10 Simplifying r = -10
| 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) | | 2.70=0.55x^2+1 | | -2x-3y=-5 | | -5(4n-4)=40 | | -5h=-20 | | 4(x-1)=2(-x) | | 4p^2+11p-45=0 | | 6(2v-2)=96 | | 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= | | 7+9+n=-9+2n+n | | 4*x^2+4*y^2-y^3=0 | | 4c-36=-8 | | y+26-8=40 | | 93=16-5p | | -12x-4=56 | | 6k-15=-33 | | 5x^2+y^2=21 | | 6x-3=17+4x | | 12/21 | | (x-3)2=12 | | 88/8 | | log(2)(5x-5)=4 | | 3x+-2=5+-3 | | 3y+1=4y+11 | | -3/5(20r-5)-(-6r) | | (x+2)(3x-1)=6 |